An engineered coiled-coil polypeptide assembled onto quantum dots for targeted cell imaging. (16th November 2015) - Yao, Ming-Hao; Yang, Jie; Song, Ji-Tao; Zhang, Lin; Fang, Bi-Yun; Zhao, Dong-Hui; Xia, Rui-Xue; Jin, Rui-Mei; Zhao, Yuan-Di; Liu, Bo
Abstract: Quantum dot (QD)–polypeptide probes have been developed through the specific metal-affinity interaction between polypeptides appended with N-terminal polyhistidine sequences and CdSe/ZnS core–shell QDs. The size and charge of a QD–polypeptide can be tuned by using different coiled-coil polypeptides. Compared to glutathione-capped QDs (QD–GSH), QD–polypeptide probes showed an approximately two- to three-fold luminescence increase, and the luminescence increase was not obviously related to the charge of the polypeptide. QD–polypeptide probes with different charge have a great effect on nonspecific cellular uptake. QD–polypeptide probes with negative charge exhibited lower nonspecific cellular uptake in comparison to the QD–GSH, while positively charged QD–polypeptide probes presented higher cellular uptake than the QD–GSH. A targeted QD–ARGD probe can obviously increase targeted cellular uptake in α v β 3 overexpressing HeLa cells compared to QD–A. In addition, QD–polypeptide probes showed lower in vitro cytotoxicity compared to the original QDs. These results demonstrate that these QD–polypeptide probes with high specific cellular uptake, high fluorescence intensity and low background noise are expected to have great potential applications in targeted cell imaging.